Molecularly targeted protease-activated probes for visualization of glioblastoma: a comparison with 5-ALA - Konečná, Dora; Výmola, Petr; Ternerová, Nikola; Výmolová, Barbora; Garcia-Borja, Elena; Mateu, Rosana; Šroubek, Filip; Pankrác, Jan; Widen, John C; Bogyo, Matthew; Netuka, David; Bušek, Petr; et al. (Journal of neurosurgery, 2024)
OBJECTIVE: The highly infiltrative growth of glioblastoma (GBM) makes distinction between the tumor and normal brain tissue challenging. Therefore, fluorescence-guided surgery is often used to improve visual identification of radiological tumor margins. The aim of this study was to evaluate the ability of recently developed molecularly targeted near-infrared (NIR) protease-activated probes to visualize GBM tissue and to compare the most promising candidate with the gold standard, 5-aminolevulinic acid (5-ALA). METHODS: Single-substrate probes 6QC-ICG and 6QC-Cy5 (cysteine cathepsin cleavable), double-substrate probes AG2-FNIR and AG2-Cy5 (cysteine cathepsin and caspase 3 cleavable), and 5-ALA were administered intravenously to mice with orthotopic tumors. Activation of the probes was also evaluated in cell cultures in vitro and in biopsy material from patients with GBM ex vivo. The tumor to normal brain tissue fluorescence ratio (TNR) was quantified in brain sections using preclinical and clinical visualization platforms, and in tissue homogenates and cell suspensions using spectrofluorimetry. Subcellular localization of the fluorophores was visualized by confocal microscopy. RESULTS: In vitro, the single-substrate probe 6QC-ICG was cleaved in glioma cells and macrophages, and the resulting fluorophore accumulated intracellularly. In experimental GBMs, both single- and double-substrate probes visualized tumor tissue, while in healthy brain tissue the signal was minimal. TNR was highest for 6QC-ICG and AG2-FNIR, but the signal intensity was higher for 6QC-ICG. Using xenograft and syngeneic mouse models, as well as human GBM biopsy material ex vivo, the authors confirmed the ability of 6QC-ICG to specifically visualize the glioma tissue using preclinical and clinical visualization platforms. Finally, a comparison with 5-ALA in animals coadministered with both compounds revealed a higher TNR for 6QC-ICG in experimental GBMs. CONCLUSIONS: The cysteine cathepsin-cleavable probe 6QC-ICG is activated by glioma cells and tumor-associated macrophages, leading to a high contrast between tumor and nontumorous brain tissue that is superior to that of the current standard, 5-ALA. In addition to a well-defined mechanism of action, protease-activated probes that use NIR fluorophores (e.g., indocyanine green) have the advantage of low absorption and scattering of the NIR light and lower tissue autofluorescence. These results suggest that 6QC-ICG has the potential to become the targeted agent in intraoperative detection of GBM tissue using fluorescence imaging.
Keywords: Animals; gliom; cystein; Cell Line, Tumor; kyselina aminolevulová; Spectroscopy, Near-Infrared; Heterografts; mouse models; blízká infračervená spektroskopie; Mice; fluorescence-guided surgery; glioblastoma; mozek; Glioma; myši; Models, Animal; glioblastom; Glioblastoma; proteasy; cathepsin; Peptide Hydrolases; Molecular Probes; oncology; Brain; Cysteine; Aminolevulinic Acid; molekulární sondy; 5-ALA; zvířata; Mice, Inbred C57BL; activity-based probes; heterografty; nádorové buněčné linie; modely u zvířat; myši inbrední C57BL